Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1037/abn0000410
|View full text |Cite
|
Sign up to set email alerts
|

Age, period, and cohort trends in mood disorder indicators and suicide-related outcomes in a nationally representative dataset, 2005–2017.

Abstract: Drawing from the National Survey on Drug Use and Health (NSDUH; N = 611,880), a nationally representative survey of U.S. adolescents and adults, we assess age, period, and cohort trends in mood disorders and suicide-related outcomes since the mid-2000s. Rates of major depressive episode in the last year increased 52% 2005–2017 (from 8.7% to 13.2%) among adolescents aged 12 to 17 and 63% 2009–2017 (from 8.1% to 13.2%) among young adults 18–25. Serious psychological distress in the last month and suicide-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
605
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 974 publications
(704 citation statements)
references
References 52 publications
(74 reference statements)
31
605
3
1
Order By: Relevance
“…Girls and young women tend to spend more time on social media than boys do, have more exposure to cyberbullying and show tendency to experience more mental health effects, 10,34 which is consistent with recent epidemiologic trends indicating that depressive symptoms, self-harm and suicidality have increased among young females in particular. [5][6][7][8][9] The context of social media use may mediate its effects. A structural equation modelling analysis of a cross-sectional survey of 910 high school students in Belgium found that, among girls, passive use of Facebook had a negative impact on mood but active use had a positive impact on perceived online social support, which in turn had a positive impact on mood.…”
Section: Are Some Individuals More Susceptible To Mental Health Effecmentioning
confidence: 99%
See 1 more Smart Citation
“…Girls and young women tend to spend more time on social media than boys do, have more exposure to cyberbullying and show tendency to experience more mental health effects, 10,34 which is consistent with recent epidemiologic trends indicating that depressive symptoms, self-harm and suicidality have increased among young females in particular. [5][6][7][8][9] The context of social media use may mediate its effects. A structural equation modelling analysis of a cross-sectional survey of 910 high school students in Belgium found that, among girls, passive use of Facebook had a negative impact on mood but active use had a positive impact on perceived online social support, which in turn had a positive impact on mood.…”
Section: Are Some Individuals More Susceptible To Mental Health Effecmentioning
confidence: 99%
“…7 Surveys of high school students in the US have shown a similar pattern for self-reported symptoms of depression, major depressive episodes and suicidality over the last 2 decades. 8,9 At the same time, social media use has increased markedly. In the US, the proportion of young people between the ages of 13 and 17 years who have a smartphone has reached 89%, more than doubling over a 6-year period; moreover, 70% of teenagers use social media multiple times per day, up from a third of teens in 2012.…”
mentioning
confidence: 99%
“…The prevalence of depression in the United States increased significantly between 2005 and 2015, most markedly among youth (Carrellas, Biederman, & Uchida, ; Weinberger et al, ). Moreover, the increase in depressive symptoms have contributed to a surge in the number of adolescent deaths by suicide between 2010 and 2015 (Twenge, Cooper, Joiner, Duffy, & Binau, ). This increase in suicide rates is common to adults as well (Curtin, Warner, & Hedegaard, ; Hedegaard, Curtin, & Warner, ), particularly those living in rural areas with greater social isolation and limited access to proper mental health care (Kegler, Stone, & Holland, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no consensus on the determinants for this rise in suicides, cross‐country evidence shows that suicide rates are related to labor market participation and unemployment rates (Milner, McClure, & De Leo, ), suggesting that one in five suicides worldwide is associated to unemployment (Nordt, Warnke, Seifritz, & Kawohl, ). Another likely explanation for the increases in suicide rates in the United States is the growing prevalence of mental health issues and depression (Twnge, Bell Cooper, Joiner, Duffy, & Binau, ).…”
Section: Introductionmentioning
confidence: 99%